ANALISIS VERBAL ABUSE TERHADAP PEMERAN WALID DALAM FILM BID’AH DALAM SUDUT PANDANG PENDIDIKAN AGAMA ISLAM - Ainul Yaqin; Muliatul Maghfiroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the forms of verbal abuse committed by the character Walid in the film Bid'ah and examine the psychological and social impacts it causes on the representation of the victim, viewed from the perspective of Islamic Religious Education. This study employs a qualitative content analysis approach, closely examining the dialogues, scenes, and narrative elements that depict the verbal communication practices of the character Walid in the film Bid’ah. The findings reveal that verbal abuse takes many forms, including intimidation, psychological manipulation, humiliation, the silencing of dissent, the distortion of religious language, and the normalization of symbolic violence. These patterns of behavior do not simply pass as fleeting harm; they settle into the psychological fabric of the victims, shaping a fragile sense of self marked by insecurity, lingering fear, sustained anxiety, and a quiet but persistent burden of guilt. In a broader social sense, they encourage silence, distance individuals from one another, and slowly construct an atmosphere where fear replaces openness within religious learning spaces. From the standpoint of Islamic Religious Education, Walid’s actions reveal a serious departure from the ethical discipline of communication taught in Islam, including hifz al-lisan (restraint of speech), qaulan sadidan (truthful articulation), qaulan ma’rufan (respectful expression), and qaulan layyinan (gentle delivery). Rather than aligning with the purpose of Islamic education—which is to cultivate moral integrity and inner calm—such conduct disrupts and weakens it. In this light, the study argues that language within religious education must be reclaimed as a medium for ethical formation and personal freedom, not reduced to an instrument of control or intimidation.